Extending the Unified Theory of Acceptance and Use of Technology (UTAUT) to understand electronic healthcare record implementation : the role of perceived goal attainment, perceived velocity and team learning behaviour - Chong, Alain Yee Loong (2019)
With the strong on-going interest and effort to push investment in the implementation of Electronic healthcare record (EHR), understanding the factors that will drive the use of the system has important scientific and practical significance. However, there is sparse literature on understanding what influence healthcare professionals (i.e. doctors, paraprofessionals and administrative personnel)’s motivation to learn and use EHR. Against this backdrop, the key objective of this thesis is to examine the factors that influence healthcare professionals’ behavioural intention to adopt and actual use of electronic healthcare record in Malaysia.